PENATALAKSANAAN FISIOTERAPI PADA PLANTAR FASCIITIS DENGAN MODALITAS TENS, IR DAN TERAPI LATIHAN DI RSUD KAJEN KABUPATEN PEKALONGAN - Fitri Milenia Sekti; Eko Budi Prasetyo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Plantar fasciitis is an inflammation of the plantar fascia. Physiotherapy problems that occur are: (1) The presence of pain in the soles of the feet, (2) The presence of muscle spasm m. gastrocnemius, (3) the limited range of motion of the bilateral ankle joint (4) the presence of bilateral ankle muscle weakness, (5) There is a decrease in functional activity, (6) The presence of tenderness in the calcaneus. This research was conducted at Kajen Hospital, Pekalongan Regency with the design used was a case study on bilateral plantar fasciitis et causa calcaneus spur patients who had been given physiotherapy interventions in the form of tens (transcutaneous eletrical nerve stimulation), infrared, and exercise therapy (free active exercise, calf raises). and active stretching). Methods of data collection and data analysis using auto history. Instruments focused on pain conditions, muscle spasm, LGS, muscle strength, functional activity. Based on the therapy carried out 4 times, the following results were obtained: (1) there was a decrease in pain from T1: 1.8 to T4: 0 (2) there was a decrease in spasm from T1: 1 to T4: 0 (3) there was an increase in ROM dorso flexion right from T1: 15o to T4: 25o, right eversion from T1: 10o to T4: 15o, dorso left flexion from T1: 10o to T4: 20o, left eversion from T1: 5o to T4: 15o, (4) there is an increase in strength muscle from T1: 4 to T5: 5 (5) there is an increase in daily functional activities. The conclusion of this study is that the TENS (transcutaneous electrical nerve stimulation), infrared, and exercise therapy (free active exercise, calf raises, active stretching) modality can reduce the problems caused by bilateral plantar fasciitis et causa calcaneus spur conditions.Plantar fasciitis is an inflammation of the plantar fascia. Physiotherapy problems that occur are: (1) The presence of pain in the soles of the feet, (2) The presence of muscle spasm m. gastrocnemius, (3) the limited range of motion of the bilateral ankle joint (4) the presence of bilateral ankle muscle weakness, (5) There is a decrease in functional activity, (6) The presence of tenderness in the calcaneus. This research was conducted at Kajen Hospital, Pekalongan Regency with the design used was a case study on bilateral plantar fasciitis et causa calcaneus spur patients who had been given physiotherapy interventions in the form of tens (transcutaneous eletrical nerve stimulation), infrared, and exercise therapy (free active exercise, calf raises). and active stretching). Methods of data collection and data analysis using auto history. Instruments focused on pain conditions, muscle spasm, LGS, muscle strength, functional activity. Based on the therapy carried out 4 times, the following results were obtained: (1) there was a decrease in pain from T1: 1.8 to T4: 0 (2) there was a decrease in spasm from T1: 1 to T4: 0 (3) there was an increase in ROM dorso flexion right from T1: 15o to T4: 25o, right eversion from T1: 10o to T4: 15o, dorso left flexion from T1: 10o to T4: 20o, left eversion from T1: 5o to T4: 15o, (4) there is an increase in strength muscle from T1: 4 to T5: 5 (5) there is an increase in daily functional activities. The conclusion of this study is that the TENS (transcutaneous electrical nerve stimulation), infrared, and exercise therapy (free active exercise, calf raises, active stretching) modality can reduce the problems caused by bilateral plantar fasciitis et causa calcaneus spur conditions.